Rotary Adsorption: Selective Recycling of CO2 in Combined Cycle Gas Turbine Power Plants - Herraiz, Laura; Palfi, Erika; Sánchez Fernández, Eva; Lucquiaud, Mathieu (Frontiers in Energy Research, 2020)
A conceptual design assessment shows that the use of structured adsorbents in a regenerative adsorption wheel is technically feasible for the application of selective exhaust gas recirculation (SEGR) in combined cycle gas turbine (CCGT) power plants. As the adsorber rotates, CO2 is selectively transferred from a flue gas stream to an ambient air stream fed to the gas turbine compressor, increasing the CO2 concentration and reducing the flow rate of the fraction of the flue gases treated in a post-combustion CO2 capture system. It imposes an estimated pressure drop of 0.25 kPa, unlike a pressure drop of 10 kPa reported for selective CO2 membrane systems, preventing a significant derating of the gas turbine. An equilibrium model of a rotary adsorber with commercially available activated carbon evaluates the inventory of the adsorbent and sizes the wheel rotor. Two rotary wheels of 24 m diameter and 2 m length are required per gas turbine—heat recovery steam generator train to achieve an overall CO2 capture level of 90% in a CCGT power plant (ca. 820 MWe) with SEGR “in parallel” to the capture plant. Two to five rotary wheels are required for a configuration with SEGR “in series” to the capture plant. A reduction of 50% in the mass of the adsorbent would be possible with Zeolite 13X instead of activated carbon, yet the hydrophilicity of zeolites are detrimental to the capacity and upstream dehydration of the flue gases is required. A parametric analysis of the equilibrium properties provides guidelines for adsorbent development. It suggests the importance of balancing the affinity for CO2 to allow the regeneration of the adsorbent with air at near ambient pressure and temperature, to minimise the inventory of the adsorbent within practical limits. An adsorbent with a saturation capacity of 8 mol/kg, a heat of adsorption from 24 to 28 kJ/mol CO2 and a pre-exponential factor of the equilibrium constant from 2 × 10–6 to 9 × 10–6 kPa−1 would result in an inventory below 200 kg, i.e., approximately the limit for the use of a single rotary wheel system.